Clean Code in Python Develop Maintainable and Efficient Code, 2nd Edition. - Anaya, Mariano (Packt Publishing, Limited, 2021)
References -- Chapter 3: General Traits of Good Code -- Design by contract -- Preconditions -- Postconditions -- Pythonic contracts -- Design by contract - conclusions -- Defensive programming -- Error handling -- Value substitution -- Exception handling -- Using assertions in Python -- Separation of concerns -- Cohesion and coupling -- Acronyms to live by -- DRY/OAOO -- YAGNI -- KIS -- EAFP/LBYL -- Inheritance in Python -- When inheritance is a good decision -- Anti-patterns for inheritance -- Multiple inheritance in Python -- Method Resolution Order (MRO) -- Mixins.